Evaluasi Kebijakan Asimilasi Narapidana pada Prison Management (Studi pada Lembaga Pemasyarakatan Kelas IIA Sidoarjo) - Sutrisno, Andi E.; Sarwono, Sarwono; Said, Moh. (Jurnal Ilmiah Administrasi Publik, 2024)
This study aims to investigate the inmate assimilation policy implemented at Class IIA Sidoarjo Penitentiary as well as to evaluate the effectiveness of the policy. The analysis in this study was conducted using the Six Sigma (DMAIC) approach which consists of the steps define, measure, analyze, improve, and control. The results showed that when viewed from the context of constraints, there was a lack of public involvement from the families of prisoners and the community as service users and policy beneficiaries, a comparison of the number of service officers lacking in providing services, lack of effectiveness and efficiency in the evaluation process and monitoring mechanism. However, in terms of implementation, the policy of assimilation of prisoners has succeeded in reducing the number of overcapacity, saving the budget for food for prisoners and accelerating the process of proposing prisoner release services from 2 months to only 14 days. This assimilation policy is proven to have an easy process and provide satisfaction with correctional services for prisoners.